The effect of ramipril in patients with impaired glucose tolerance - Akbulut, M; Karaca, I; Ikay, E; Özbay, Y; Arslan, N (Medimond S R L, 2001)
In this study we aimed to research the effect of ramipril in normotensive cases with impaired glucose tolerance according to criteria of American Diabetes Association (ADA). One hundred fourty seven normotensive cases with impaired glucose tolerance (IGT) were included in this study. For average 21+/-6 months, 75 cases were given 2.5 mg ramipril+diet, 72 cases were given placebo+diet. Clinical and laboratory investigations of all cases were recorded by doing 12 week intervals. At the end of the study, in the ramipril group the number of cases whose impaired glucose tolerance improved was higher (p=0.001). However in placebo group the number of the cases that newly diabetes developed and who had major cardiovascular events (MI, cardiac arrest, stroke, revascularization procedure, heart failure) were higher (p=0.033, p=0.021). While ramipril increases the conversion of IGT to normal in normotensive cases with IGT, decreases major cardiovascular events and development of de novo diabetes.
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Converting-Enzyme-Inhibition; Insulin Sensitivity; Randomized Trial; Hypertension; Coronary; Hyperinsulinemia; Mortality; Acarbose; Disease; Niddm